Salafiyah: Sejarah dan Konsepsi - Imdad Rabbani (Tasfiyah: Jurnal Pemikiran Islam, 2017)
This article discusses salafiyah in both history and conception. This is important to be studied further, because lately, especially in Indonesia there is an interesting phenomenon in which there is one group to identify themselves as salafi, slightly different from the mainstream of Muslims and claiming to be more strictly committed following the manhaj salaf al-sālih and the scholars which is in line with their understanding. One characteristic of this class is that it tends to be too strict in understanding religion so that it does not correspond to the wasatiyyah (mid) character of Islam. The consequence is that the exclusiveness shown by this group towards other Muslims, does not acknowledge the scholarly orbit of scholars outside the scholars who are inconsistent with their manhāj and consider their group alone who present the teachings of Islam in line with the understanding of the salaf. Another consequence is to easily mislead other Muslims when there is a difference between their understanding and the group. For this purpose, this paper attempts to retrace what is meant by the term salaf, the history of salafiyah development and some of the issues relating to first refer to its meaning on al-Qur’an, hadith, language and term.